Implementasi Pendidikan Karakter Perspektif Nilai-Nilai Pendidikan Islam di Pondok Pesantren Provinsi Lampung - Bahri, Saiful; Sunarto, Sunarto (CV. Creative Tugu Pena, 2022)
The purpose of this study is to describe the implementation of character education in the perspective of Islamic educational values ??at the Al Hikmah Islamic Boarding School in Bandar Lampung, the Al Huda Prengsewu Islamic Boarding School, the Ushuludin Islamic Boarding School, South Lampung. Identifying what factors are the obstacles in implementing character education from the perspective of Islamic education values ??at Al Hikmah Islamic Boarding School Bandar Lampung, Al Huda Prengsewu Islamic Boarding School, Ushuludin Islamic Boarding School, South Lampung. This type of research is descriptive qualitative with. Collecting data using observation, interviews, and documentation. The analysis technique consists of three streams of activities that occur simultaneously, namely data reduction, data presentation and conclusion drawing. The findings of this study are that the implementation of character education in the perspective of Islamic educational values ??among students shows a fairly good character, one of which is caused by optimal character development in educational institutions. The implementation of character education should not be left to religious teachers only, and Islamic boarding schools but also school principals, teachers, administrative staff, janitors, canteen guards and even parents at home have an important role in the implementation of character education. Another factor that hinders the implementation of character values ??is that the kyai are too busy in activities outside the Islamic boarding school so that many students are not given enough attention. Keywords: Education Character, Islamic Education Value, Islamic Education